A atividade da modelagem de artefatos técnicos e sua potencialização na formação para uma engenharia criativa: estudo de casos no projeto BAJA UFMG - Jarbas da Cunha e Silva (2023)
This research aimed to understand the development process of technical artifacts through the case study of the BAJA project at the UFMG School of Engineering. This formative experience involves “engineering practice” in the universe of mechanical engineering when students – apprentice engineers - are encouraged to develop and build an offroad vehicle prototype through the design process and engineering design. Such activity concerns idealizing a solution, validating it, and achieving propositions in functional artifacts. It is in the activity of modeling three technical artifacts - the Rear Steering Mechanism, the Pneumatic Steering Link and components of the Continuous Variable Transmission mechanism (CVT) - that this research has focused, when the student is encouraged to explore possibilities and convert restrictive situations and undetermined problems into coherent solutions. The question of the research was then to comprehend how it is possible to foster creative engineering from the process of developing a technical artifact, even with the technical-scientific rationality, and the functionalist way of thinking in terms of deterministic foundations that are predominance in Engineering. To subsidize the research, we seek theoretical deepening in the field of engineering design, education and acquisition of skills, activity theory, among other adjacent perspectives and approaches; and in authors such as Cross, Schön, Simondon, Simon, Alexander, Bucciarelli, Dorst, Boden, Petroski, Dreyfus, Vygotsky, Dewey, Engeström, among others. This research is eminently qualitative, descriptive, and analytical. As a method and guidance, the approach of the Grounded Theory was adopted and, from the analysis of the actions taken and the processes involved, as well as interviews, observation, and documentary research, the codification and systematization of the data proceeded, so it was possible to establish three fields or dimensions of activity as categories of analysis - design space, experimentation, and adaptation - which allowed us to elaborate a theoretical construct and enabled a qualitative analysis of design activity in fulfilling the question and objective of the research. Field research and analysis revealed that by facing the indetermination inherent in the design process, while students seek to support themselves in disciplinary theoretical knowledge when they manipulate parametric data from design space, the experience also leads to experiential knowledge, making room to manifest intuition, memory and the combinatory capacity of imagination, which ultimately allows them to elaborate alternatives and integrate restrictive boundary conditions, and even supplant the indetermination creating new compositions. This process is made possible by reflection and analysis of design space data in experimentation phase and through synthesis capacity that leads the student to build form and structure to a proposal of a solution by attributing stability to the stresses verified between the constituent elements of the problem promoting the realization from the initial proposition, or their revisions generated by experimentation, making them in solutions adapted to the context in which they are, functional and creative. Thus, this research defends the thesis that, in the face of the restrictions and uncertainties of the design process, as well as the limitations that technical-scientific knowledge may impose, students reflect on the activity, evaluates and adjusts their actions by activating knowledge, disciplinary and experiential - these arising from the practical experience itself in dealing with indetermination to which the project is subject - to achieve propositions in a technical artifact and promoting to a large extent an effective education in engineering, not just that based on analytical thinking and disciplinary knowledge, but also in a more creative engineering education, since creativity is generated in the very experience of “technical doing” and the investigative process triggered by the initial problem.